MISI DAN PEMURIDAN KRISTEN GEREJA PANTEKOSTA DI INDONESIA (GPDI) DI SULAWESI UTARA: TANTANGAN ATAU PELUANG DI ERA DIGITAL - Meily Meiny Wagiu; Semuel Selanno; Harun Samuel Sajanga; Englin R. Manua; Agnes Clararita Kota (Sekolah Tinggi Teologi Arastamar Bengkulu, 2025)
This study investigates the mission and discipleship practices of the Indonesian Pentecostal Church (GPdI) in North Sulawesi in the digital age, integrating the local cultural values of Mapalus and the motto “Si Tou Timou Tumou Tou.” Employing a qualitative phenomenological approach, data were collected through in-depth interviews with 12 church leaders and members, participatory observations, and analysis of church policy documents. Four key findings emerged: (1) digital engagement strategies utilizing social media platforms and instant messaging apps to extend ministry outreach; (2) local cultural resonance as a basis for deeper spiritual meaning; (3) strengthening of the church’s spiritual identity through synergies between Pentecostal theology and Minahasan traditions; and (4) the need for the development of online training (e-learning) to facilitate ongoing discipleship. The study’s implications suggest that blending digital technology with local culture enhances discipleship effectiveness while reinforcing church community cohesion. Recommendations include the creation of local wisdom–based e-learning modules and establishing a theologically and technically trained digital ministry team.